RANCANG BANGUN SISTEM INFORMASI MANAJEMEN GEREJA BERBASIS WEB DI GEREJA HKBP TEMBESI - Benny; Saragih, Saut Pintubipar (LPPM Universitas Putera Batam, 2024)
HKBP Trans Barelang Church has a system that runs without using computer-based or digital application-based information systems. The issue at the HKBP Trans Barelang church is the difficulty faced by congregation members in accessing congregation data. Registering as a member also involves a more complicated registration process, where you have to go to the church officials and fill out paper forms. Furthermore, one of the church's business processes, such as collecting tithes, offerings, or donations, is not flexible. This happens because to provide these things to the officials, one has to personally visit the congregation officials and fill out information on paper related to tithe and donation data. This research was conducted using the waterfall method, where the design and development of the system follow the processes in the waterfall stages. The results of this research show that the HKBP church information system provides convenience to officials in managing church administration, handling tithes and offerings, and making announcements about church activities using a system that is easier to reach and access. The HKBP Trans Barelang Church information system makes it easy to store congregation member data in the form of a database stored on the church's server.